The temperate forest of the state of Nuevo León: sustainable management for goods and environmental services - Návar-Cháidez, José de Jesús (Instituto de Ecología, A.C., 2016)
In this research paper, information is presented on the dasometric features of standing volume, diameter, top height, tree density, diameter distributions, tree and stand productivity, aboveground biomass, carbon in aboveground biomass and the tree biological diversity of temperate forests of the state of Nuevo Leon, Mexico. This information was derived from 63 inventoried sites within the framework of the forest inventory of 2004-2006. It is concluded that temperate forests are in juvenile state with diameter distributions skewed to the right, with low tree density, low densities of standing volume, biomass and carbon stocks. Tree productivity is also small since it does not surpass on the average 0,36 cm y-1. Tree diversity at the site scale is also small since less than four species are found on the average on these sites. There was statistical evidence that productivity is related to tree diversity and structural diversity in a positive and linear manner. Therefore, there is a great potential to sustainably manage these forests for a wide range of goods and services. It is recommended a light management for goods for 15 years and to carry on the appropriate silvicultural practices to enhance tree diversity as well as structural diversity to increase productivity.